Making America Great Again, 2024 - Shimshon Bichler; Jonathan Nitzan (The Bichler & Nitzan Archives, 2024)
In 2019, we published a RWER paper assessing Trump's promise to `Make America Great Again'. Here are updates of two key charts from this paper.
Keywords: P1; F1; 330; capitalist mode of power; America's decline; economic policy; Donald Trump